Shoreline dynamics of an urbanised estuarine beach under the influence of changing sediment budgets - Kennedy, David M.; Yuan, Runjie; McCarroll, R. Jak; Liu, Jin; Beetham, Eddie; Ierodiaconou, Daniel (Frontiers in Earth Science, 2025)
Sandy beaches within estuaries and bays are dynamic landforms. As many large urban centres are located on the margins of these enclosed marine systems the beaches that form their shoreline are often subject to significant management intervention. Understanding the geomorphological evolution of these beaches and their future evolutionary pathways is therefore difficult as it requires detangling human modification of sediment budgets from natural variability. In this study, a multiproxy shoreline analysis is undertaken of a 3 km long fetch-limited beach in Port Phillip Bay, Australia. The beach is divided into several sediment compartments delineated by groynes and natural rocky outcrops, each exhibiting shoreline rotation on the seasonal scale leading to lateral profile movement of up to 40 m. The medium-term (last 30 years) sediment budget is approximately +3,000 m3/year due to longshore drift and nourishment. Beach nourishment over the last 40 years accounts for 25% of the total sediment budget. This has balanced the loss of natural sediment supply from cliff erosion caused by erosion protection works such as seawalls. It is concluded that groyne construction has enhanced shoreline rotation patterns on a seasonal scale. Overall, this study shows how human modifications to the sediment budget were initially negative but now maintain a functioning geomorphic environment. Full consideration of the seasonal-scale shoreline dynamics is required to understand longer (decadal-scale) beach evolution.